Psychiatric symptoms in patients with metastatic ALK-positive NSCLC treated with third-generation ALK-inhibitors: a brief review and case series (Journal of Medical Science, 2024)
Central nervous system (CNS) disorders have been observed in patients treated with anaplastic lymphoma kinase (ALK) inhibitors and particularly with lorlatinib. According to a real-world pharmacovigilance study, the most frequent psychiatric symptoms were mood disorders, psychotic disorders, anxiety, agitation and irritability. Nonetheless, it is still unclear how ALK tyrosine kinase inhibitors (ALK-TKIs) may lead to psychiatric adverse events, although ALK seems to be involved in dopamine D2 receptor endocytosis in response to prolonged dopamine stimulation. Here, we report three cases of patients treated with ALK inhibitors in a single Italian Centre who developed psychiatric disorders.